The Importance of Melatonin Detection in Pediatric Deaths. Issue 1 (March 2019) - Labay, Laura M.; Kraner, James C.; Mock, Allen R.; Sozio, Thomas J.
Melatonin is an endogenous hormone that regulates sleep patterns. It is available in varying formulations and dosages and is marketed as a natural substance that can alleviate insomnia. Recent news reports indicate that melatonin has been administered without appropriate authorization in daycare settings. Even though lethal outcomes have not been solely attributed to exogenous melatonin overdose, it has been relevant to select police and postmortem investigations. A quantitative liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay was developed for the analysis of biological specimens. Results of 22 positive blood samples were evaluated based upon gender, age, and melatonin concentration from cases submitted by clinical, police, and death investigation agencies. Two cases are described. In Case 1, a 9-month-old was found unresponsive after cosleeping with a sibling. Allegations included exposure to an unspecified pesticide and dextromethorphan, and consumption of half a cigarette. There was admitted use of melatonin. Melatonin was quantified in blood and gastric fluid at concentrations of 13 ng/mL and 1200 ng/mL, respectively. In Case 2, a 13-month-old was found nonresponsive in a shared room. Melatonin was found within some of the sippy cups. The infant was extremely warm to the touch. Resuscitative efforts were unsuccessful and death was pronounce3d. Analysis showed a result of 210 ng/mL in blood. The presented quantitative LC-MS/MS method can successfully be applied to evaluate exposure to exogenous melatonin. Toxicology testing can assist in the investigation of these case types by substantiating the purposeful administration of melatonin.